Delineasi DAS dan Elemen Model Hidrologi Menggunakan HEC-HMS Versi 4.4 - M. Baitullah Al Amin; Mona Foralisa Toyfur; Widya Fransiska; Ayu Marlina (Department of Civil Engineering and Planning, Faculty of Engineering, Sriwijaya University, 2020)
The watershed delineation process is needed and has an essential role in various water resource projects. This study aims to examine the GIS processing function embedded in the latest HEC-HMS software version 4.4 for the delineation of watershed and elements of the hydrological model. In comparison, watershed delineation was also carried out by using ArcGIS software. The area of study is the Bendung subbasin located in Palembang City, where terrain data used is a National DEM data with a spatial resolution of 8 m (0.27 arc-second). The results showed that the boundaries and area of the watershed produced by HEC-HMS 4.4 and ArcGIS showed the same characteristics. The river network produced by the two software shows a slight difference even though the flow patterns are similar. It shows that the level of accuracy and quality of the delineation produced by the HEC-HMS 4.4 is excellent. Besides, elements of the hydrological model can be generated automatically which is not found in previous versions. It allows users to more quickly simulate detailed hydrological models with a large number of elements. Therefore, the use of GIS functions in HEC-HMS 4.4 must be encouraged for various analysis purposes in water resources projects.